Conscious Consumption: Empowering Middle School Students as Agents of Change - Cruz, Agnes Luiza F. da; Ramos , Heidy Rodriguez (ANAP Brazil, 2025)
Objective – This study aims to explore effective strategies for integrating environmental education into the curriculum of the Final Years, based on students’ perceptions of conscious consumption, with the goal of promoting the adoption of responsible environmental practices. Methodology – The research adopted a qualitative and exploratory approach, using the case study as the methodological strategy. Data collection was conducted at a private school in a high-income area of South São Paulo, with the participation of 360 students from the 8th and 9th grades. Originality/Relevance – The study fills a theoretical gap by addressing the disconnect between theory and practice in teaching about conscious consumption, highlighting the need for the integration of environmental education and the importance of involving families in school initiatives. Results – The results revealed that, although many students understood the concepts of conscious consumption, they faced significant barriers to applying them in practice, such as social pressure and lack of access to sustainable products. The disconnect between theory and practice was a central finding, highlighting the need to involve families in educational initiatives. Theoretical/Methodological Contributions – The study highlights the importance of a continuous and interdisciplinary approach to environmental education and suggests that small changes in students’ behavior may serve as a positive indicator of change. Social and Environmental Contributions – The research suggests that schools should promote sustainable practices in an integrated and collaborative manner, contributing to the development of more conscious citizens who are better prepared to address environmental challenges.